2018
DOI: 10.1002/cncr.31850
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in gallbladder cancer pathogenesis: Insights from a multi‐institutional comparison of tumor mutations

Abstract: Background Although rare in the United States, gallbladder cancer (GBCA) is a common cause of cancer death in some parts of the world. To investigate regional differences in pathogenesis and outcomes for GBCA, tumor mutations were analyzed from a sampling of specimens. Methods Primary tumors from patients with GBCA who were treated in Chile, Japan, and the United States between 1999 and 2016 underwent targeted sequencing of known cancer‐associated genes. Fisher exact and Kruskal‐Wallis tests assessed differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 43 publications
9
55
1
Order By: Relevance
“…Only one ISH study on the MET gene copy number in GBCs was found in the literature, and it revealed that no amplification was detected in 89 cases of GBCs [25]. The previous studies using NGS data reported that MET amplification was rare event in GBCs [30,31]. In our study, no MET amplification was detected by NGS method in 17 available cases.…”
Section: Discussioncontrasting
confidence: 43%
“…Only one ISH study on the MET gene copy number in GBCs was found in the literature, and it revealed that no amplification was detected in 89 cases of GBCs [25]. The previous studies using NGS data reported that MET amplification was rare event in GBCs [30,31]. In our study, no MET amplification was detected by NGS method in 17 available cases.…”
Section: Discussioncontrasting
confidence: 43%
“…We generate ortho-and heterotopic GBCs featuring the most frequent genetic alterations (p53 together with mutant KRAS, as well as p53 in conjunction with mutant ERBB2). Tumors develop with 100% penetrance and can be generated with and without loss of Pten, a gene that is inactivated in a subset of human GBCs [18,31]. Since murine Erbb2 is known to be less oncogenic than its human counterpart, we introduced the human ERBB2 gene [32].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the ERBB2-gene are among the most common genetic alterations in gallbladder cancer [17,18,[24][25][26]. To assess their potential as oncogenic drivers in our organoid based GBCs, we stably introduced human ERBB2 and two ERBB2 mutants (ERBB2 S310F and ERBB2 V777L ) by retroviral transduction into gallbladder organoids, in which p53 loss had been induced by Cas9-mediated genome editing ( Figure 4A).…”
Section: Overexpression Of Activating Erbb2 Mutants Give Rise To Gbcmentioning
confidence: 99%
See 2 more Smart Citations